ANALISIS PENGARUH BUDAYA ORGANISASI DAN KOMITMEN TERHADAP KINERJA DOSEN PERGURUAN TINGGI SWASTA - Ahmad Dirwan (Jurnal Dinamika Pendidikan, 2014)
This reserach was conducted to determine the influence of organizational behavior and commitment towards lecturers’ performance at private universities in Jakarta. The method used in this research is the survey method. The samples in this research were 90 lecturers of private universities who were selected randomly. The technique used to analyze the obtained data was a path analysis by employing SPSS program. The results indicated that: (1) there was influence of organizational behavior towards the lecturers’ performance, (2) there was influence of commitment towards the lecturers’ performance, (3) there was influence of organizational behavior and commitment simultaneously towards the lecturers’ performance.Keywords: organizational behavior, commitment, lecturer performance